Scientific Opinion on the re-evaluation of sodium stearoyl-2-lactylate (E 481) and calcium stearoyl-2-lactylate (E 482) as food additives - EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) (EFSA Journal, 2013)
Following a request by the European Commission, the Panel of Food Additives and Nutrient Sources added to Food (ANS) was asked to deliver a scientific opinion on the safety of sodium stearoyl-2-lactylate (E 481, SSL) and calcium stearoyl-2-lactylate (E 482, CSL) when used as food additives. SSL and CSL are used as emulsifiers and stabilizers. An Acceptable Daily Intake (ADI) of 20 mg/kg bw/day for SSL and CSL (either singly or in combination) was established in 1974 by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). The Scientific Committee on Food (SCF) endorsed this ADI of 20 mg/kg bw/day in 1978. The biological fate of CSL is comparable in rodent and non-rodent species. The acute oral toxicity in rats is low. Subacute and subchronic oral toxicity studies with SSL and CSL in rats and dogs revealed a NOAEL of 5 % in the diet. Neither SSL and CSL nor their breakdown products stearic and lactic acid raise concern for genotoxicity. The NOAEL in a one-year oral toxicity study with SSL in rats was 2214 mg/kg bw/day for males and 2641 mg/kg bw/day for females. No data on reproductive toxicity and carcinogenicity were available. However, no reproductive or carcinogenic effects are expected since the products of hydrolysis, stearic and lactic acid are constituents of natural food and part of endogenous metabolism in mammals. The Panel concluded that based on the NOAEL of 2200 mg/kg bw/day derived from the one-year toxicity study in rats and an uncertainty factor of 100, an ADI of 22 mg/kg bw/day for sodium stearoyl-2-lactylate (E 481) and calcium stearoyl-2-lactylate (E 482) either singly or in combination can be established. The estimated exposure to SSL and CSL occurs mainly via the consumption of flavoured fermented milk products including heat treated products, bread and rolls and fine bakery wares and is below the ADI of 22 mg/kg bw/day for all the adult population including the elderly, but exceeds the ADI for other groups of the population at mean level and for all groups of the population at high level.